The Dialogue of Absence - Richard Stamelman (Studies in 20th & 21st Century Literature, 1987)
The Dialogue of Absence
Keywords: Edmond Jabès; dialogue; poetry; poetics; communication; isolation; self; consciousness; speech; word; identity; others